2022
DOI: 10.1017/cjn.2022.19
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mechanical Ventilation in Guillain–Barré Syndrome with Axonal Subtypes

Abstract: Background: The early clinical predictors of respiratory failure in Latin Americans with Guillain–Barré syndrome (GBS) have scarcely been studied. This is of particular importance since Latin America has a high frequency of axonal GBS variants that may imply a worse prognosis. Methods: We studied 86 Mexican patients with GBS admitted to the Instituto Nacional de Ciencias Médicas y Nutrición Salvador Zubirán, a referral center of Mexico City, to describe predictors of invasive mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
2
1
Order By: Relevance
“…This may be the result of genetic and environmental differences, as demyelinating variants are more frequent in white populations, while axonal variants are more frequent in Latin American and Asian populations [ 41 ]. The proportion of axonal variants and mortality rate we observed are consistent with pre‐COVID‐19 rates, where axonal subtypes accounted for up to 60% of cases, with an overall mortality rate as high as 12% [ 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 85%
“…This may be the result of genetic and environmental differences, as demyelinating variants are more frequent in white populations, while axonal variants are more frequent in Latin American and Asian populations [ 41 ]. The proportion of axonal variants and mortality rate we observed are consistent with pre‐COVID‐19 rates, where axonal subtypes accounted for up to 60% of cases, with an overall mortality rate as high as 12% [ 42 , 43 , 44 ].…”
Section: Discussionsupporting
confidence: 85%
“…AMAN has a worse functional outcome compared to AIDP, and a previous study in our country reported a higher frequency of mechanical ventilation in axonal variants. 1,26 In our study, we did not observe differences between the electrophysiological variants requiring prolonged mechanical ventilation. Severe axonal damage (distal CMAP ≤1.0 mV) is associated with a worse outcome.…”
Section: Discussioncontrasting
confidence: 43%
“…42 The proportion of axonal variants and mortality rate we observed is consistent with pre-COVID-19 rates, where axonal subtypes accounted for up to 60% of cases with an overall mortality rate as high as 12%. [43][44][45] Interestingly, when comparing mRNA-based versus adeno-vectored vaccines, we observed a higher incidence ratio for mRNA platforms. These variations in such large samples suggest that genetic and environmental factors may result in increased susceptibility to GBS among recipients of specific SARS-CoV-2 vaccines.…”
Section: Discussionmentioning
confidence: 93%